The Relative Efficacy of Chemically Diverse Small-Molecule Enzyme-Inhibitors Against Anticoagulant Activities of African Spitting Cobra (Naja Species) Venoms - Chowdhury, Abhinandan; Lewin, Matthew R.; Zdenek, Christina N.; Carter, Rebecca; Fry, Bryan G. (Frontiers in Immunology, 2021)
African spitting cobras are unique among cobras for their potent anticoagulant venom activity arising from strong inhibition of Factor Xa. This anticoagulant effect is exerted by venom phospholipase A2 (PLA2) toxins whose activity contributes to the lethality of these species also elude effective neutralisation by currently available antivenoms. Previous work demonstrated varespladib was able to neutralize this toxic action but only a single high concentration of varespladib was tested. The present work builds upon this previous work by testing the efficacy of varespladib at lower concentration against the African spitting cobra species Naja ashei, N. katiensis, N. mossambica, N. nigricincta, N. nigricollis, N. nubiae, and N. pallida. In addition, we examined previously noted, unexpected, cross-reactivity of the metalloprotease inhibitor prinomastat with PLA2. We have again observed tha t prinomastat (and to a lesser extent, marimastat) inhibited the FXa-inhibiting PLA2 toxins but the exact mechanism by which this effect occurs remains unclear. Due to logistical (cold-chain requirement) and efficacy (cross-reactivity across snake species) limitations of traditional antivenoms, particularly in developing countries where snakebite is most common, these small molecule inhibitors (SMIs) might hold great promise as initial, field-based, treatments for snakebite envenoming as well as addressing some fundamental limitations of antivenom where administered in the clinical setting.